THE CAPACITY OF PRAGMATICS IN ESL TEACHING OF ENGLISH STUDENTS IN BULELENG REGENCY - Kadek Heni Oktarina Wisudayanti; Putu Desi Anggerina Hikmaharyanti (SPHOTA: Jurnal Linguistik dan Sastra, 2021)
This study is focused on the capacities of pragmatics in ESL teaching and limited to three essential discussions; first, the investigation of teaching pragmatics relevancy stated on pragmatics elements, second, the presentation of the effective ways in teaching pragmatics by applying SURE steps (Brock and Nagaska, 2005), and the elaboration of pragmatics effects towards ESL learners. It is necessary to conduct a research of pragmatics capacities in ESL teaching. Due to the problems discussed, the theories suggested in this research include pragmatics definition, pragmatic competence, pragmatic elements and SURE method. Then, the method applied in this research is descriptive qualitative in nature and the data are from the 3rd semester of STKIP Agama Hindu Singaraja students. The data analysis is performed to investigate the relevancy of pragmatics in ESL teaching, the pragmatics teaching methods, and the effect of pragmatics towards ESL learners. This study finds pragmatics is a relevant point to be taught in the language classroom due to language is an arbitrary. Through SURE methods, students are expected to comprehend the language used in contexts. Pragmatics affects the ESL learners to be sensitive about the surroundings, other cultural interactions, also how they must behave towards circumstances as ESL learners. Abstrak Penelitian ini difokuskan pada kapasitas pragmatik dalam pengajaran ESL dan dibatasi pada tiga diskusi esensial; pertama, investigasi relevansi pengajaran pragmatik yang tertuang pada unsur-unsur pragmatik, kedua, penyajian cara efektif dalam pembelajaran pragmatik dengan menerapkan metode SURE (Brock dan Nagaska, 2005), dan penjabaran efek pragmatik terhadap peserta didik ESL. Untuk itu perlu dilakukan penelitian tentang kapasitas pragmatik dalam pengajaran ESL. Berdasarkan permasalahan yang dibahas, maka teori yang disarankan dalam penelitian ini meliputi pengertian pragmatik, kompetensi pragmatis, unsur pragmatis dan metode SURE. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan data dari mahasiswa-mahasiswa STKIP Agama Hindu Singaraja semester 3. Analisis data dilakukan untuk mengetahui relevansi pragmatik dalam pembelajaran ESL, metode pembelajaran pragmatik, dan pengaruh pragmatik terhadap peserta didik ESL. Studi ini menemukan bahwa pragmatik adalah poin yang relevan untuk diajarkan di kelas bahasa karena bahasa bersifat sewenang-wenang. Melalui metode SURE, mahasiswa diharapkan memahami bahasa yang digunakan dalam konteks. Pragmatik mempengaruhi mahasiswa ESL untuk peka terhadap lingkungan sekitar, interaksi budaya lainnya, juga bagaimana mereka harus berperilaku terhadap keadaan sebagai peserta didik ESL.